Market Competition, Perceived Environmental Uncertainty, Supply Chain Management Systems, and Organizational Performance: Hotel Starred in Bali Province, Indonesia - I Nyoman Sunarta; Abdul Rohman; Warsito Kawedar (International Journal of Supply Chain Management, 2020)
Abstract-The purpose of this study is to examine the effect of market competition (MC) and perceived environmental uncertainty (PEU) on the use of supply chain management (SCM) information and the utilization of SCM information on organizational performance, based on contingency theory. Data were collected using a questionnaire sent directly to the main managers of three, four and five-star hotels in the Province of Bali, Indonesia. This study uses organizational level analysis units. The data obtained were 122 and analyzed using WarpPls 6.0. The results showed that MC and PEU had a positive and significant effect on the utilization of SCM information (broad scope, timeliness, aggregation, and integration). In addition, the use of SCM information, affects the performance of three, four and five-star hotels in Bali Province, Indonesia.